Ekplorasi 'Efek Wow': Daya Tarik Wisata dan Kualitas Pelayanan Memicu Niat Kunjungan Kembali - Ramadhan, Bayu; Hidayah, Asmi Ayuning (Sains: Jurnal Manajemen dan Bisnis, 2024)
This research aims to explore the extent of the influence of tourist attraction and service quality on the intention to revisit, mediated by satisfaction. The research focuses on visitors to local tourism sites in Banyumas Regency. It employs a quantitative approach by distributing questionnaires to 121 respondents via Google Form. Respondents were selected based on specific criteria or characteristics, namely, aged between 17-40 years old and have visited at least one tourist destination in Banyumas Regency within the last year. Based on the analysis conducted using SEM AMOS, it was found that tourist attraction influences the intention to revisit but does not affect visitor satisfaction. Meanwhile, service quality influences visitor satisfaction but does not affect the intention to revisit. Visitor satisfaction can influence the intention to revisit. However, visitor satisfaction does not mediate either tourist attraction towards the intention to revisit or service quality towards the intention to revisit.